Relaţia dintre Carte sau Lumină…, Snagov, 1699, şi Procanon […] alcătuit şi întocmit de Petru Maior, 1783 - Adina Chirilă (Revista de Istorie și Teorie Literară)
The substance of the present paper represents a text comparison between two books of theological polemic and philosophy, one from the 17th century, the other written at the end of the 18th century. The first one, Carte sau lumină…, Snagov, 1699, is the Romanian version of an Orthodox Greek text, both of them being printed in Wallachia in the context of advertising and imposing the Church Union upon the Orthodox believers in Transylvania; the latter is written by a Greek-Catholic scholar, Petru Maior, who displays religious ideas and beliefs similar to those existing in the previously mentioned book, in order to determine a reconsideration of the Greek-Catholic Church principles, and politics, by the high clergy. Knowing the fact that Carte sau lumină… has been in circulation in Transylvania, particularly in Blaj, our purpose was to see how strong the direct relation between the two books was, in terms of quotation, explicit or not. We conclude that, although the two books share ideas, principles, comments and interpretations of controversial biblical texts, Petru Maior quotes rather scarcely from the 17th century book; instead, he mentions and cites different other writers and texts containing the same type of information, to justify its position and convince his readers through transfer of multiple authority.